Utilization of Biang Fish Flour (Ilisha elongata) as an Enrichment Material for Sago Noodles Nutrient Value - Suparmi, Suparmi; Sumarto, Sumarto; Afriana, Umi; Hidayat, Taufik (International Journal of Biomaterials, 2022)
This study aims to determine the appropriate concentration of lead fish meal for enriching the nutritional value of sago noodles favored by consumers. The method used is an experimental design using Completely Randomized (CRD) with 4 concentration levels of lead fish meal, namely, 4% without a lead fish meal (M0), 6% (M1), 8% (M2), and 10% (M3). The analysis of sago noodles was performed and proximate by the AOAC method; amino acids by HPLC; fatty acids by GC; and minerals by HPLC. The results of the showed that the study getting the best treatment was a concentration of 8% (M2) with the characteristics of whole sago noodles’ appearance: attractive, grayish-white color; a distinctive aroma of sago noodles with a hint of fish; a specific taste typical of sago noodles and fish prickly taste; delicious; slightly chewy texture. Sensory evaluation with a taste value of 8.9, an aroma of 8.6, a visual value of 8.9, and a texture value of 8.8. Its nutritional content is 5.58% protein content, air 22.35%, ash 1.69%, fat 1.41%, and carbohydrates 68.29%. The proximate values are protein 5.58%, water content 22.35%, ash 1.69%, fat content 1.41%, and carbohydrates (different) 68.29%. The mineral content is Ca.P.I, Mg, Zn, and Fe. Amino acids consist of 8 types of essential amino acids, namely, histidine, arginine, threonine, valine, alanine, methionine, isoleucine, leucine, phenylalanine, and 7 types of nonessential amino acids, namely, aspartic acid, glutamic acid, serine, glycine, tyrosine. Its fatty acid profile has 13 components of unsaturated fatty acids and 17 components of saturated fatty acids.